(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: The fascia iliaca compartment block is commonly used for postoperative analgesia after hemiarthroplasty. However, the method often fails to adequately manage pain due to frequent sparing of the lateral femoral cutaneous nerve. This randomised controlled study was conducted to compare the efficacy of lateral femoral cutaneous and femoral nerve blocks compared to fascia iliaca compartment block for postoperative pain management following hemiarthroplasty. Methods: Sixty patients were randomly assigned to either the fascia iliaca compartment (FIC) block group or the lateral femoral cutaneous nerve and femoral nerve (LFCN plus FN) block group. All patients received a subarachnoid block for surgery. Pain was assessed using a visual analogue scale (VAS) in the recovery room. When patients reported VAS score 3 or 4, the FIC and LFCN plus FN blocks were performed according to group allocation. VAS scores were reassessed 20 minutes after the blocks and recorded. Subsequently, the pain was assessed using VAS at two-hour intervals until the patients required rescue analgesia. Results: The VAS scores differed significantly between the two groups. In the LFCN plus FN block group, 13.3% reported VAS 0, 30% reported VAS 1, and the rest reported VAS 2. In the FIC block group, 53.3% reported VAS 2, and 46.7% reported VAS 3. None reported VAS 0 in the FIC group. The average time to demand rescue analgesia was 4.9 (0.8) hours in the FIC group and 9.4 (1.5) hours in the LFCN plus FN group. Adjusted time based on age, sex, body mass index, and Anesthesiologists class for the FIC block group was 6.8 (0.9) hours, while the LFCN plus FN block group recorded 7.5 (0.8) hours (P=0.003). Conclusion: Administering the LFCN and FN block separately but simultaneously provides better postoperative analgesia than the conventional FIC block following hemiarthroplasty.